2009
DOI: 10.1016/j.geomorph.2007.06.026
|View full text |Cite
|
Sign up to set email alerts
|

The influence of elevation uncertainty on derivation of topographic indices

Abstract: Digital elevation models at a variety of resolutions are increasingly being used in geomorphology, for example in comparing the hypsometric properties of multiple catchments. A considerable body of research has investigated the sensitivity of topographic indices to resolution and algorithms, but little work has been done to address the impact of DEM uncertainty and elevation value error on derived products. By using higher resolution data from the Shuttle Radar Topography Mission -of supposed higher accuracy -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…This makes matching these points more difficult globally; hence we did not match them in the edges of imageries. As previous studies suggested (e.g., Frey and Paul, 2012;Hebeler and Purves, 2009), although some grid points that may have an influence on the hypsography of small glaciers are not equal to each other, local differences in these data have only a small influence on the hypsography of large glaciers.…”
Section: Topographic Informationmentioning
confidence: 67%
“…This makes matching these points more difficult globally; hence we did not match them in the edges of imageries. As previous studies suggested (e.g., Frey and Paul, 2012;Hebeler and Purves, 2009), although some grid points that may have an influence on the hypsography of small glaciers are not equal to each other, local differences in these data have only a small influence on the hypsography of large glaciers.…”
Section: Topographic Informationmentioning
confidence: 67%
“…A DEM quality depends on several factors including the acquisition system; methodology and algorithms; complexity of the terrain; grid spacing and data characteristics [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The error in several DEM data is widely explored on reasons and significances, which a quality of DEM be influenced by on several factors, as well as sensor types, algorithm, terrain type, grid spacing and characteristics (Hebeler and Purves 2009). A variety of DEMs on free provided data, including the 10 m DEM produced by the Geographical Survey Institute (GSI) of Japan (GSI-DEM), Advanced Space Borne Thermal Emission and Reflection Radiometer-Global Digital Elevation Model (ASTER GDEM), Shuttle Radar Topography Mission (SRTM), Global Multi-resolution Terrain Elevation Data 2010 (GMTED2010), Hydrological data and maps based on Shuttle Elevation Derivatives at multiple Scales (HydroSHEDS) and Global 30 Arc-Second Elevation (GTOPO30) is useful to model nearly the terrain of earth in worldwide.…”
Section: Introductionmentioning
confidence: 99%